Senior Management Program in the transformational leadership of directors of the Yanahuanca District, Pasco, 2017 - Capcha-Hinostroza, Karla E. (2020)
The present investigation has like objective to apply the Program of High Management in the Transformational Leadership of the directors of educational institutions of the district of Yanahuanca, Pasco. The PAG has been designed with a methodology that contemplates a high conten of social skills and directives based on the theory  of  Abraham Maslow's theory, Aldelfer's ERG theory and the Motivational theory of Homeostasis; highlighting transformational leadership actions, managerial tolos, critical visión and optimal skills,where participants interact and cooperate to produce knowledge from analysis, reflection and discussion in groups.. The methods used are problem-based learning (PBL) and case study (CS).The validity of the instrument was realized by expert judgment and reliability through the Cronbach's Alpha Index.; within theresults was obtained in the entry application sometimes never, and in the output application, the scale was improved from normally to always, reflectin a X2 was used, obtaining 40,190, concluding that there is significant improvement of the top management program in the transformational leadership of directors.